PENGARUH PROMOSI SEPEDA MOTOR MEREK HONDA TERHADAP MINAT BELI KONSUMEN PADA PT.GLOBAL JAYA PERKASA PEKANBARU - Gita Ria Angrayni Pandia; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to analyze the influence of motorcycle promotion Honda brand in increasing consumer buying interest PT. Global Jaya Perkasa Pekanbaru. The independent variables are promotions measured using advertising, personal selling, sales promotion, public relations and direct sales. The dependent variable is consumer buying interest as measured by transactional interest, refrensial interest and preferential interest, explorative interest. The sample in this research is consumer of PT. Global Jaya Perkasa Pekanbaru was taken randomly using Slovin formula which amounted to 93 respondents. Based on the results of data analysis it can be concluded that the promotion gives a significant influence on consumer buying interest PT. Global Jaya Perkasa Pekanbaru. Keywords : Product promotion and consumer buying interest